City-forming Elements on the Image of the City of Makassar - Armiwaty Armiwaty; Mithen Mithen; Raeny Tenriola Idrus (PINISI Discretion Review, 2023)
city is formed or can be identified by the presence of its constituent elements, where through these elements the image of a city will appear. Tamalanrea Subdistrict is included in the City Service Center area, and as one of the City Service Center areas, this area must be an area that is quite easy to recognize. This is related to the image of the area which shapes the perception of residents and newcomers to the area. This study aims to identify elements that have the potential to shape the image of Makassar City, especially in the city service center area in Tamalanrea District. The research method is a qualitative method with the object of research namely the Perintis Kemerdekaan corridor which is included in the Tamalanrea District area. The discussion is descriptive with library research, namely the study of literature and other informative media. The results showed that the image of the Tamalanrea sub-district area along the Perintis Kemerdekaan street corridor was strong enough as a center for education and research activities on an international, national and regional scale. However, better integration of city imagery is needed in order to create a more comprehensive city image